The Linking of Entrepreneurship Education and Entrepreneurial Readiness: The Mediating Role of Entrepreneurial Ecosystem - Nita Ambarita; Suwatno; Dian Herdiana Utama (Dinamika Pendidikan, 2024)
This study aims to determine the linkage between Entrepreneurship Education and Entrepreneurial Ecosystem on Entrepreneurship Readiness among students of SMKN Tembilahan, Indragiri Hilir Regency. This research is a quantitative study with a research population of as many as 312 students, and the research sample was 175 students. This research instrument is a questionnaire developed from each research variable. The data were analyzed using Structural Equation Modeling (SEM) analysis with the Partial Least Square method. The results showed that entrepreneurship education has a positive and significant effect on entrepreneurial readiness. The mediation test results confirm that the entrepreneurial ecosystem doesn’t mediate the effect of entrepreneurship education on entrepreneurial readiness. This indicates that schools may not have adequate infrastructure to stimulate entrepreneurial interest among students. The study’s findings offer significant insights into how entrepreneurship education and entrepreneurial ecosystem can help vocational students to enhance entrepreneurial readiness.